Charlie Ant’ Insect Bite Associated Preseptal Cellulitis - Patricia Ann John; Sylves Patrick; Ngoo Qi Zhe; Wan Hazabbah Wan Hitam; Adil Hussein (2020)
Preseptal cellulitis is a worrying condition in children. One of the commonest causes is from insect bite. The Charlie ant or Paederus fuscipes has been reported as a dermatitis-causing agent due to its toxin, pederin. The aim is to report a case of preseptal cellulitis secondary to Charlie ant insect bite. A two-year-old girl presented with bilateral eyelid swelling, redness, and pain for two days. The Charlie ant was at the nasal bridge before the presentation. There was presence of generalised bilateral eyelid swelling, redness with multiple pustules, excoriated skin, and eye discharge. She was admitted and started on antibiotics. The pustules ruptured, left the skin exposed, and her condition improved. Preseptal cellulitis is a contiguous spread of infection. An attack by Charlie ant has become a public health concern. There is no specific treatment for this condition. Early detection may prevent complications.